Measuring changes in the optic nerve sheath diameter in patients with idiopathic normal‐pressure hydrocephalus: a useful diagnostic supplement to spinal tap tests. (15th December 2016) - Ertl, M.; Aigner, R.; Krost, M.; Karnasová, Z.; Müller, K.; Naumann, M.; Schlachetzki, F.
Abstract : Background and purpose: Cerebrospinal fluid (CSF) removal improves clinical symptoms of many patients with idiopathic normal‐pressure hydrocephalus (iNPH). The aim of this study was to investigate the correlation of changes in the optic nerve sheath diameter (ONSD) with patient responses to CSF removal. Methods: Transorbital ultrasonography was performed to obtain ONSD measurements in 31 patients with iNPH before and after lumbar puncture. Measurements were obtained while patients were supine and upright. Changes in the ONSD between supine and upright positions [ONSD variability (ONSD‐V)] were assessed and compared with those in 60 healthy volunteers. ONSD‐V was correlated with relative changes in a validated iNPH severity (Boon) score. Results: Mean pre‐puncture ONSD‐V was significantly lower in healthy volunteers and patients with no response to CSF removal (Fisher test) [0.05 ± 0.14 mm (SD)] than in responsive patients [0.37 ± 0.20 mm (SD), P < 0.001]. ONSD‐V predicted response to the spinal tap test (odds ratio, 0.30; 95% confidence interval, 0.12–0.75 mm, P = 0.011). The higher the ONSD‐V, the better the therapeutic effect ( χ 2 = 14.980, P < 0.001). The post‐spinal tap test ONSD‐V correlated significantly with clinical severity in the motor portion of the Boon score [0.16 ± 0.23 mm (SD), P = 0.003]. Conclusions: The ONSD‐V before and after spinal tap test correlated well with the clinical effects of CSF removal. Transorbital ultrasonography seems to be a reliable, safe add‐on to the Fisher test and may support selection of patients for shunt intervention.